1999
DOI: 10.1016/s0022-5347(05)68797-6
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Laparoscopic Versus Open Radical Nephrectomy

Abstract: Retroperitoneal laparoscopic nephrectomy for kidney cancer requires further assessment. It seems to have several advantages over open radical nephrectomy, and to be effective and safe for less than 50 cm. renal tumors but a risk of spillage cannot be ruled out for larger tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(44 citation statements)
references
References 29 publications
0
36
0
7
Order By: Relevance
“…The laparoscopic group experienced less postoperative pain and returned to normal activities sooner. From a sample of 58 patients, Abbou et al [3] showed that the laparoscopic (retroperitoneal) group experienced less pain in the postoperative period compared to the open nephrectomy group (2b). In the fourth study, Pace et al [93] compared laparoscopic (transperitoneal) with open nephrectomy in a series of 61 patients (2b).…”
Section: Nephrectomy For Malignancymentioning
confidence: 99%
“…The laparoscopic group experienced less postoperative pain and returned to normal activities sooner. From a sample of 58 patients, Abbou et al [3] showed that the laparoscopic (retroperitoneal) group experienced less pain in the postoperative period compared to the open nephrectomy group (2b). In the fourth study, Pace et al [93] compared laparoscopic (transperitoneal) with open nephrectomy in a series of 61 patients (2b).…”
Section: Nephrectomy For Malignancymentioning
confidence: 99%
“…using the retroperitoneal laparoscopic approach. 7 Patients who underwent hand-assisted retroperitoneoscopic radical nephrectomy revealed significantly less postoperative pain, shorter intervals to the resumption of oral intake and more rapid return to normal activities compared to patients who underwent open radical nephrectomy. Although the advantages in comparison with the open procedure were obvious, morbidity concerning the longer incision is thought to be a possible demerit of the hand-assisted procedure against standard laparoscopic procedure.…”
Section: Discussionmentioning
confidence: 90%
“…6 Although the transperitoneal approach has been commonly performed, recently some authors reported the retroperitoneal approach as a feasible and effective technique. 7,8 Gill et al . reported that retroperitoneoscopy offered several unique advantages, including expeditious access to the renal artery and vein allowing early ligation, extra fascial mobilization of the kidney and en bloc removal of the adrenal gland, recapitulating the principle of open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The ef®cacy of laparoscopic radical nephrectomy for renal cell cancers has been reported in several studies. Abbou et al [33] reported on patients undergoing laparoscopic or open radical nephrectomy (29 in each group). They reported a mean operative duration of 2.4 h for the laparoscopic and 2 h for the open group, a respective mean blood loss of 100 mL vs 285 mL and a mean hospital stay of 4.8 days and 9.7 days.…”
Section: Laparoscopic Radical Nephrectomymentioning
confidence: 99%